Myelin Basic Protein and Cardiac Sympathetic Neurodegeneration in Nonhuman Primates - Jeanette M. Metzger; Helen N. Matsoff; Don Vu; Alexandra D. Zinnen; Kathryn M. Jones; Viktoriya Bondarenko; Heather A. Simmons; Colleen F. Moore; Marina E. Emborg (Neurology Research International)
Minimal myelination is proposed to be a contributing factor to the preferential nigral neuronal loss in Parkinson’s disease (PD). Similar to nigral dopaminergic neurons, sympathetic neurons innervating the heart have long, thin axons which are unmyelinated or minimally myelinated. Interestingly, cardiac sympathetic loss in PD is heterogeneous across the heart, yet the spatial relationship between myelination and neurodegeneration is unknown. Here, we report the mapping of myelin basic protein (MBP) expression across the left ventricle of normal rhesus macaques (n = 5) and animals intoxicated with systemic 6-OHDA (50 mg/kg iv) to model parkinsonian cardiac neurodegeneration (n = 10). A subset of 6-OHDA-treated rhesus received daily dosing of pioglitazone (5 mg/kg po; n = 5), a PPARγ agonist with neuroprotective properties. In normal animals, MBP-immunoreactivity (-ir) was identified surrounding approximately 14% of axonal fibers within nerve bundles of the left ventricle, with more myelinated nerve fibers at the base level of the left ventricle than the apex p<0.014. Greater MBP-ir at the base was related to a greater number of nerve bundles at that level relative to the apex p<0.05, as the percent of myelinated nerve fibers in bundles was not significantly different between levels of the heart. Cardiac sympathetic loss following 6-OHDA was associated with decreased MBP-ir in cardiac nerve bundles, with the percent decrease of MBP-ir greater in the apex (84.5%) than the base (52.0%). Interestingly, cardiac regions and levels with more MBP-ir in normal animals showed attenuated sympathetic loss relative to areas with less MBP-ir in 6-OHDA + placebo (r = −0.7, p<0.014), but not in 6-OHDA + pioglitazone (r = −0.1) subjects. Our results demonstrate that myelination is present around a minority of left ventricle nerve bundle fibers, is heterogeneously distributed in the heart of rhesus macaques, and has a complex relationship with cardiac sympathetic neurodegeneration and neuroprotection.